THE ROLE OF PUNJABI POETS IN THE UNIVERSAL SUFISM WITH SPECIAL REFERENCE OF PEACEFUL COEXISTENCE - Aslam, Dr. Sobia; Riaz, Muhammad (Al-Irfan, 2022)
The vital role has been played by the Sufi poets for universal peaceful coexistence. Islam as religion flourished under the umbrella of mysticism. Sufis of various schools of thoughts associated with people because they were human being with caring their race, color, creed and even their religion did not matter. They used the public mode of expression; poetry in the local languages and in this regard Punjabi poets occupy the highest rank. They preached love and peace for all in a very popular and simple language and avoid any kind of philosophical labyrinth. People that were suppressed and oppressed gathered round them as they felt sheltered there. In this article we clarify the role of Punjabi Sufi Poets in the universal Sufism with the special reference of peaceful coexistence. An analytical type of research methodology is adopted to make it clear that the Punjabi poets did a lot to preach love and peace that afterwards became the part of the movement that brought Islam all over the world.